White-collar crime in academia: Trends in digital academic dishonesty over time and their effect on penalty severity. (November 2019) - Etgar, Shir; Blau, Ina; Eshet-Alkalai, Yoram
Abstract: This study explored patterns of change over time in penalties for conducting academic dishonesty (AD), following a previous study (Friedman Blau & Eshet-Alkalai, 2016) that reported lower penalties for digital AD offenses compared to analog ones across two years. In the present study, we examined whether this trend changes over time, and what could explain it. We offered two contradicting hypotheses: the regulations hypothesis suggests that the gap between penalties for analog and digital AD caused since it takes time for academic institutes to adjust their regulations to digital dishonesties. Therefore, this gap will diminish and eventually disappear. The perception hypothesis suggests that the penalty gap will remain stable, since it reflects the perception of digital AD as a "white-collar" offense. Contrary to previous studies that used self-reported measurements of AD perceptions, this study analyzed Disciplinary Committee's protocols, which contains a more objective descriptions of type of AD, student's explanations, and penalty types. These protocols provide information about the actual behavior of students and faculty, and not about their opinions. We analyzed the entire volume of 628 university's protocols collected during four consecutive years. Findings clearly demonstrated that the trend of lower penalties for digital offenses remained stable across four years. Results support the perception hypothesis, suggest that this phenomenon relates to the perception of digital AD as a "white-collar crime". Like other white-collar crimes, is perceived as less harmful and therefore, punished less severely than other crimes. This claim is also supported by our findings that motivations to behave unethically, which students reported to the Discipline Committee, influenced penalties' severity in analog, but not in digital settings. Unexpectedly, a consistent gender-gap was found in penalties' severity for both digital and analog offenses, indicating that women were punished more severely than men. This dissimilarity in penalizing AD offenses remained stable over the studied period. We discuss theoretical and practical implications of these findings. Highlights: Patterns of change in penalties for digital academic dishonesty were explored. 628 Disciplinary Committee's protocols were analyzed for a 4-years period. We found that digital offenses were penalized less severely than analog ones. The digital-analog gap in penalties' severity remained stable across four years. Gender gap in penalties: women were penalized more severely than men.